Comparative binding study of anti-tuberculosis drug pyrazinamide with serum albumins. Issue 89 (9th September 2016) - Chaturvedi, Sumit Kumar; Siddiqi, Mohammad Khursheed; Alam, Parvez; Zaman, Masihuz; Khan, Rizwan Hasan
Abstract : The interaction of anti-tuberculosis drug pyrazinamide (PYZ) with serum albumins (HSA and BSA) has been studied using spectroscopic and molecular docking approaches. Abstract : The interaction of anti-tuberculosis drug pyrazinamide (PYZ) with serum albumins (HSA and BSA) has been studied using spectroscopic and molecular docking approaches. The effects of PYZ on the protein conformation, topology and stability were determined using Circular Dichroism (CD), Dynamic Light Scattering (DLS) and Differential Scanning Calorimetry (DSC). The obtained binding constant ( K b ) was ∼10 4 M −1 for both HSA and BSA, although a higher affinity of PYZ was found with BSA. A higher value for the Gibbs free energy reflects that PYZ interacts more favourably with BSA. A reduction in the hydrodynamic radii and increase in the secondary structural content of the protein confirm that the serum albumins stabilize on binding with PYZ. Furthermore, elevation of the transition melting point also supports the stabilizing action of PYZ. Furthermore, site specific markers and a molecular docking study confirmed the binding location of PYZ with HSA and BSA. The present study will be helpful for understanding the binding of PYZ and associated alterations in the stability and conformation of serum albumins.